Fasciolosis: a case report presentation - Cazorla Portillo, Ernesto (2024)
Fasciolosis (liver fluke disease) is a zoonosis of significant public health relevance, caused by parasites of the genus Fasciola, specifically of the species Fasciola hepatica, a helminth of the class Trematoda, which exhibits a lanceolate morphology and is involved in the zoonotic cycle through contamination of bodies of water and aquatic vegetation, including watercress, by means of metacercariae, its infective form. Their biological cycle includes a migration phase from the host’s intestine to the liver, where they mature and settle in the bile ducts, causing pathological changes such as direct hepatic lesions, bile duct obstruction and a systemic inflammatory response. Clinically, these events manifest through predominantly hepatic and gastrointestinal symptoms secondary to hepatic involvement, which can escalate to severe complications such as cirrhosis and hepatic abscesses in the absence of early diagnosis and adequate treatment. We present the case of a 54-year-old female patient who was admitted to the emergency room with a condition characterized by headache, vomiting, cough, palpitations and dyspnea on exertion. The initial diagnostic evaluation, guided by the ultrasound presentation of choledocholithiasis, led to an endoscopic retrograde cholangiopancreatography (ERCP) that revealed the presence of a single papilla. This finding, along with the described symptoms, facilitated the diagnosis of hepatic fasciolosis caused by Fasciola hepatica, which was later removed. Likewise, it underscores the importance of including this parasitosis as a differential diagnosis for hepatic and gastrointestinal diseases, particularly in compatible epidemiological contexts or a history of exposure to contaminated freshwater sources.